Pengetahuan Sejarah Dekolonialisasi Pernanan Pendidikan dan Implementasi Hukum Islam di Indonesia - Ryan Kurniawan (Universitas Indraprasta PGRI Jakarta, 2019)
Role, Education, and Implementatation Islamic law developed along with the development of Islam in various regions, causing Islamic law to have different styles in each region it came. Indonesia is one of these regions. Differences or uniqueness that arise together with the acceptance of Islamic law in Indonesia by experiencing various kinds of changes in accordance with the time, space and place of the law applied. The role of various kingdoms in disseminating Islamic teachings is legitimate evidence, how Islam becomes an integral part of the Indonesian Nation. Changes began to occur when the Dutch colonial government ruled Indonesia. The receptio in complexu theory, and the receptie theory are proof of the attachment of the Dutch legal order in Indonesia which began in the V.OC era. Independence as the starting point of the struggle to reduce the influence of the two theories with efforts to decolonize Islamic law through receptie exit theory. This theory directs that the development of Islamic law in Indonesia is based on Pancasila and the 1945 Constitution, which is marked by the emergence of KHI as a guideline compiled and formulated to fill a substantial legal vacuum in the courts in the religious court that tried the Islamic civil case in 1991